Autonomic Neurons with Sympathetic Character Derived From Human Pluripotent Stem Cells. (31st January 2019) - Saito‐Diaz, Kenyi; Wu, Hsueh Fu; Zeltner, Nadja
Abstract: We describe an in vitro differentiation protocol to derive autonomic neurons of the peripheral nervous system with the character of postganglionic sympathetic neurons from human pluripotent stem cells. This protocol has been used to generate autonomic neurons from healthy embryonic stem cells as well as from patient‐derived induced pluripotent stem cells, which were previously used to model familial dysautonomia, a genetic childhood disorder affecting the autonomic nervous system. Here, we describe each step in detail that is necessary to successfully derive these cells. First, we generate neural crest cells, which are purified using fluorescence‐activated cell sorting. This is followed by intermediate culture as neural crest spheroids, where the cells can be expanded, and lastly long‐term differentiation into neurons. The cells have morphological and molecular characteristics of autonomic neurons and thus can be employed to study diseases affecting the autonomic nervous system. © 2019 by John Wiley & Sons, Inc.